Moderate dieting causes 5-HT2C receptor supersensitivity. - Cowen, P; Clifford, E; Walsh, A; Williams, C; Fairburn, C (1996)
Dieting is a widespread behaviour in developed countries, which in predisposed individuals can lead to the development of clinical eating disorders such as bulimia nervosa and anorexia nervosa. We studied the effect of moderate dieting in healthy women on the prolactin response to the serotonin (5-HT) receptor agonist, m-chlorophenylpiperazine (mCPP), a measure of the sensitivity of post-synaptic 5-HT2C receptors. Dieting significantly increased the prolactin response to mCPP and lowered plasma concentrations of the 5-HT precursor, tryptophan. We propose that dieting in women is associated with the development of functional supersensitivity of 5-HT2C receptors, probably in response to lowered levels of brain 5-HT. Alterations in brain 5-HT neurotransmission could play a part in dieting-induced dysregulation of eating and the development of clinical eating disorders in predisposed individuals.